THE EFFECT OF SOME INVIROMENTAL FACTORE IN SOME GROWTH TRAITS AND MILK PRODUCTION IN TURKISH AWASSI SHEEP. - AL-SAMARAI, Wafaa I.; Al-KAZRAJI, Wasan J.; Al-JELAWI, Jafar R.; Ajeel, Hamood M. (Diyala Agricultural Sciences Journal, 2015)
The study was involved 450 records of the lamb birth weight and 185 records of the weight at weaning and growth rate to 433 records the qualities of milk yield of a flock of Awassi Turkish sheep belong to the Research station, Ruminants in the Abu Ghraib (20 km west of Baghdad) of the Public Authority agricultural Research for the period from 01.01.2007 until 31.12.2008, in order to study the effect of some environmental factors in a number of growth traits (weight at birth , weaning and growth rate weighted from birth to weaning) as well as the attributes of milk production (milk production daily and the total length of the milk season) were also regression to the decline in growth characteristics of the three above-mentioned all of the weight of the mother at birth and the age of weaning.The results showed that the average weight at birth and weight at weaning and growth rate weighted from birth to weaning were 3.93 ± 0.06 kg and 29.05 ± 0.49 kg and 24.61 ± 0.46 kg, respectively, as the overall average for the production of milk daily and total lactation length 1.025 ± 0.021 kg and 122.201 ± 2.61 kg and 115.81 ± 0.93 days.It has been shown that the month of birth significantly affected (P<0.05) in growth traits and milk production, also results showed the presence of highly significant differents for the year of birth in birth weight, and the effect was highly significant for the type of birth in all the characteristics of growth studied, also showed that the gender of the lamb significant effect (p <0.05) in weight at birth and highly significant in weight at weaning and growth rate weighted, and did not notice any significant effect on the type and sex of the baby in the qualities of milk production of the three studied while it became clear that the sequence of birth effect highly significant in all the qualities of milk production studied and the effect of birth weight significantly in production milk daily, kidney and the disappearance of his moral influence in the length of lactation. It was observed that the lack of moral decline of the three growth traits studied on the weight of the mother and the age of weaning. It was concluded that the majority of the factors under study showed a significant impact in the performance of Awassi sheep which requires study and determine the impact of interest and administrative aspects of the herd to increase performance and maximize economic return.